2016
DOI: 10.1038/ismej.2016.129
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into a dinoflagellate bloom

Abstract: In coastal waters worldwide, an increase in frequency and intensity of algal blooms has been attributed to eutrophication, with further increases predicted because of climate change. Yet, the cellular-level changes that occur in blooming algae remain largely unknown. Comparative metatranscriptomics was used to investigate the underlying molecular mechanisms associated with a dinoflagellate bloom in a eutrophied estuary. Here we show that under bloom conditions, there is increased expression of metabolic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 77 publications
1
53
0
Order By: Relevance
“…Specialization on certain vitamers/precursors could play an important role in niche partitioning and/or species succession in phytoplankton blooms. Expression of B 12 ‐remodeling genes during a dinoflagellate bloom (Gong et al ., ) lends support to the potential importance of remodeling strategies for competitive phytoplankton dynamics. That HMP concentrations can exceed thiamine concentrations in marine ecosystems (Carini et al ., ) is further evidence of the ecological relevance of precursors, especially considering that thiamine degrades under UV radiation (Okumura, ).…”
Section: Rethinking Vitamin Cycling In Phytoplankton Communitiesmentioning
confidence: 64%
“…Specialization on certain vitamers/precursors could play an important role in niche partitioning and/or species succession in phytoplankton blooms. Expression of B 12 ‐remodeling genes during a dinoflagellate bloom (Gong et al ., ) lends support to the potential importance of remodeling strategies for competitive phytoplankton dynamics. That HMP concentrations can exceed thiamine concentrations in marine ecosystems (Carini et al ., ) is further evidence of the ecological relevance of precursors, especially considering that thiamine degrades under UV radiation (Okumura, ).…”
Section: Rethinking Vitamin Cycling In Phytoplankton Communitiesmentioning
confidence: 64%
“…This study speculated that high expression of these genes is related to the competitive advantages of dinoflagellates against other competing organisms in the water column during the bloom formation. Metatranscriptome comparison of bloom sites with non-bloom sites showed that 42% of the taxonomically-annotated sequence reads in bloom site were from dinoflagellates, whereas only~20% of reads from the non-bloom site were from dinoflagellates [80]. In addition, metatranscriptome data under bloom conditions indicates there is increased expression of genes involved in cellular metabolism due to the higher growth rate of dinoflagellates during HABs.…”
Section: Habs Dynamicsmentioning
confidence: 99%
“…The first application of DinoSL in dinoflagellates metatranscriptomics was documented by Lin et al [26]. Since then, a number of studies has been reported regarding metatranscriptomics approaches to elucidate the dynamic nature of species' interactions during HABs and gene expression patterns during bloom development [20,79,80].…”
Section: Habs Dynamicsmentioning
confidence: 99%
“…, ) and in a bloom forming dinoflagellate the gene expression patterns indicate that nitrogen starvation leads to the upregulation of genes involved in lipid metabolism and cell cycle arrest (Gong et al . ), which is a precursor of PCD. However, the two processes (PCD and lipid accumulation due to nitrogen starvation) have not been examined at the same time in the same culture of C. reinhardtii .…”
Section: Introductionmentioning
confidence: 99%